The Role of Work Motivation as a Mediating Variable In The Influence of Information Technology and Competence on Employee Performance of Bromo Tour Drivers in Malang City - Pratama, Fernando Ananda (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study explores how information technology and employee competence shape the performance of Bromo tour drivers in Malang City, with work motivation positioned as a mediating factor. The topic is relevant because digital transformation in the tourism sector has significantly changed service delivery and operational practices. Background Problems: The core issue examined is whether information technology and competence can effectively enhance work motivation and, in turn, improve employee performance, leading to a central research question on the real impact of these variables within nature-based tourism operations. Novelty: The novelty of this study lies in simultaneously assessing technology use, competence, and motivation among Bromo tour drivers—a group that has received limited scholarly attention despite their increasing reliance on digital navigation tools, booking platforms, and communication systems. Research Methods: The research employs an explanatory quantitative approach using the SEM-PLS method. A total of 44 official Bromo tour drivers were selected through purposive sampling based on their work experience and their ability to operate digital applications relevant to daily operations. Finding/Results: The findings reveal that information technology significantly enhances work motivation, whereas competence does not show a significant effect on either motivation or performance. Moreover, work motivation does not mediate the relationship between information technology, competence, and employee performance. Conclusion: The study highlights the need for technology-oriented competency development and more structured motivation strategies—such as digital training, performance-based incentives, and professional guidance—to strengthen service quality and improve tourist satisfaction in the Bromo tourism area.